Montenegro and the War in Ukraine: A Divided Country - Irena Femic; Mina Medjedovic (Athens Journal of Mass Media and Communications, 2023)
It has been 100 days since the War in Ukraine began. On this occasion, the Embassy of Ukraine in Montenegro organized a support march in Cetinje. In contrast, this city has also been known for protests to support the Russian invasion. Similar contrasts are visible in the decision of Montenegro to join EU sanctions against Moscow in April, including a ban on Russian airlines in its airspace and Russian state media. Sanctions were adopted after three failed attempts due to differences in opinions within the Government of Zdravko Krivokapić. Despite this, the stand of Montenegrin citizens is straightforward: every invasion should be condemned. Montenegro's controversial and complicated relations with Russia also reflect political and media coverage of the War in Ukraine. This paper aims to show how the War in Ukraine has been presented in the Montenegrin media and what are the official views of the Montenegrin establishment. We will analyze in what way and how (un)biased the Montenegrin media presented the development of the situation from day today and how this reporting influenced the formation of public opinion.